Visões cartográficas de Itabaiana-SE - Santos, Jadson de Jesus (2014)
The traditional cartography aims to find points and sites themselves, often leaving aside other important elements to the location shown on the map. In this perspective, the cartography seems to be just a framework of point locations and places, strategic or not. The making of a map is typically linked to trained professionals for that which, in fact, is required when taken into account the scientific and the use of the techniques necessary for the accurate location. However, one must take into account that there are other ways of cartography that do not necessarily require location accuracy, but rather perception. The map, in addition to the location function is for social, anthropological, historical, biological or even geographic locations studies and also be the product of these studies. In this sense, create new methods and meanings to the cartography can lead to several problems found in the disciplinary field, it is necessary to open the doors to the outside, to the new. That´s what the construction of a new cartography need: insert new insights and perspectives about the forms of representation, without losing the essential character of a map of the location. Considering the strategic importance of the Itabaiana city for the state of Sergipe, we understand that a study involving the view that social groups have of the city is quite relevant. The work has as main objective to analyze the socioeconomic, cultural and environmental potential of Itabaiana from the social cartography produced by students of the campus of the Federal University of Sergipe in the municipality. Specific objectives were proposed: to identify UFS students views from socioeconomic, cultural and environmental Itabaiana city; interpret the social cartography produced by students; and present views of students on campus of the UFS in Itabaiana through social cartography in order to facilitate studies that emphasize the importance of social cartography to aid more effective public policies that take into account aspects often unnoticed by the look manager. It was found from the views of respondents that social cartography is a tool that enables reading of the perceptions of places, so as to contribute for the planning and better distribution and allocation of public resources, as well as it serves as a source of research for several areas of knowledge.